SYSTEMATIC LITERATURE REVIEW: PENERAPAN GAME EDUKASI DIGITAL DALAM PEMBELAJARAN MATEMATIKA - Fadlilah, Siti Ni’matul Ummi; Afifah, Dian Septi Nur; Nugraha, Aldila Wanda (De Fermat : Jurnal Pendidikan Matematika, 2026)
Research on the use of educational games in mathematics instruction has grown significantly in recent years, in line with the increasing integration of technology in education. However, existing research findings remain scattered across various publications, necessitating a systematic review to obtain a comprehensive overview. This study aims to analyze research trends regarding the use of educational games to enhance mathematical concept understanding using the Systematic Literature Review (SLR) method. Articles were retrieved from several databases, namely Scopus, Sciedu Press, Google Scholar, DOAJ, and SINTA. A total of 50 articles published between 2018 and 2026 were analyzed based on predetermined inclusion and exclusion criteria. The results indicate that the majority of studies employed experimental and Research and Development (R&D) methods and were conducted at the Junior High School and Elementary School levels. Additionally, the dominant variables studied include learning motivation, learning outcomes, and mathematical concept understanding. The aim of this study is to analyse the development trends of research on the application of digital educational games in mathematics education; (2) to examine the effectiveness of the application of digital educational games in various contexts of mathematics education; and (3) to identify research gaps as a basis for the development of future research in the field of mathematics education